PERAN PEKTIN DAN SUKROSA PADA SELAI UBI JALAR UNGU (The Role of Pectin And Sucrose On Purple Sweet Potato Jam) (Jurnal Teknologi Pangan, 2013)
Purple  sweet  potato  (Ipomoea  Batatas  L.  Poir)  is  vines  that  contain  lots  of anthocyanins  (11,  051  mg/100  gr)  and   fiber  (3%) is highly  beneficial  to human health (Suprapta,  2006). Jam  is  a  made  form  count,  rest  of  sieve  or  mill  fruit  cooked  with  sugar  to mixed  thick  (Susanto,1993).The  process  of  jams  faced  purple  sweet  potato  is  not  formation gels. This study aims to determine the effect of the addition of pectin and sucrose on the quality of purple sweet  potato jam. This  research    using  a  Complete  Randomized  Design    factorial patterns with two factors and three replications. The first factor : addition of pectin   (0,5%, 1% , 1,5%) and the second factor : sucrose (55%, 60%,65%).The best results was pectin (1%) and sucrose (65%) resulting purple sweet potato jam with content of anthocyanins (9.935%), water 54.85%, water activity 0.86, crude fiber 51.62%, total of dissolved solids  60.94%, pH 3.4  and a  smear of  jam 12.2 %.  The  color  of  favorite  values  (111.5),  taste  (142),  flavor  (129)  and texture (122.5).Key words : purple sweet potato, jam, pectin, sucrose